Evaluation of the Implementation of the Pre-PON 2024 Regional Training Center Program for West Nusa Tenggara Province - S, M. Ariy Dermawan; Supriyatnak, Kokom (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to evaluate the implementation of the Regional Training program for NTB Province for PON 2024. The type of research used is descriptive with a qualitative approach. Data sources are obtained from primary data and secondary data. The data collection techniques used were observation, interviews and documentation. The evaluation model used in this research is the CIPP model (context, input, process, product). The research results show that the context aspect, namely in the form of policies and objectives, has been well defined by KONI NTB. In the input, process and product aspects, there are significant obstacles. Where the availability of facilities and infrastructure is still lacking, budget support is still inadequate. In terms of success in qualifying athletes, there has actually been an increase, with more than 254 athletes qualifying to take part in the upcoming PON 2024. However, this achievement is the result of the involvement of elements outside KONI NTB, namely Sports Management, as well as athletes and coaches who are active independently. KONI should have taken a key role, but in reality it was replaced by other parties who actually have roles and responsibilities that are no greater than KONI.